Starlikeness of Normalized Bessel Functions with Symmetric Points - Maryam Nazir (Hindawi Limited, 2021)
Bessel functions are related with the known Bessel differential equation. In this paper, we determine the radius of starlikeness for starlike functions with symmetric points involving Bessel functions of the first kind for some kinds of normalized conditions. Our prime tool in these investigations is the Mittag-Leffler representation of Bessel functions of the first kind.